Perlindungan Hukum Bagi Anak yang Lahir di Penjara Dalam Perspektif Hak Asasi Manusia - Agnetha, Bianca; Cahyaningtyas, Irma (Universitas Semarang, 2022)
The purpose of this study is to determine the government's efforts in providing legal protection for children born in prison through related laws and regulations and also how legal protection for children born in prison from human rights perceptions. The research method used is normative juridical research. The results showed that in the latest Correctional Law, there are changes and additional provisions regarding children born in prisons. The first provision is that there is a change in the age limit for children to live in prison with their mothers, who used to only reach the age of 2 (two) years to the age of 3 (three) years. Second, the children of female prisoners are placed in a separate room that is kept clean and suitable for the child's growth and development. Third, in the event that the child of a female prisoner is a child with special needs, the child may be placed in a disability services unit. Tujuan dari penelitian ini untuk mengetahui upaya pemerintah dalam memberikan perlindungan hukum bagi anak yang lahir di penjara melalui peraturan perundang-undangan yang terkait dan juga bagaimana perlindungan hukum bagi anak yang lahir di penjara dari persepktif hak asasi manusia. Metode penelitian yang digunakan adalah penelitian yuridis normatif. Hasil penelitian menunjukan bahwa dalam Undang-Undang Pemasyarakatan terbaru, terdapat perubahan maupun ketentuan tambahan mengenai anak yang lahir di penjara. Ketentuan pertama adanya perubahan mengenai batas umur anak dapat tinggal dipenjara dengan ibunya, yang dahulu hanya mencapai usia 2 (dua) tahun menjadi usia 3 (tiga) tahun. Kedua, anak dari narapidana perempuan ditempatkan pada ruangan terpisah yang terjaga kebersihannya dan layak untuk tumbuh kembang anak. Ketiga, dalam hal anak dari narapidana perempuan merupakan anak yang berkebutuhan khusus, anak dapat ditempatkan pada unit layanan disabilitas.